Cobalt oxide loaded graphitic carbon nitride as adsorptive photocatalyst for tetracycline removal from aqueous solution. (March 2019) - Niu, Jinye; Xie, Yi; Luo, Haiqiong; Wang, Qian; Zhang, Yongkui; Wang, Yabo
Abstract: The treatment of antibiotic-containing wastewater is of great importance due to the potential threats of antibiotics to human and the ecosystem. We reported the preparation of cobalt oxide loaded graphitic carbon nitride (CoO/g-C3 N4 ) by an impregnation-calcination method for tetracycline (TC) removal from aqueous solution. The developed CoO/g-C3 N4 exhibited high adsorption capacity and fast adsorption kinetic for TC due to the complexation of TC with surface loaded CoO. In particular, 7%CoO/gC3 N4 3 sample presented a maximum TC adsorption capacity of 391.4 mg g −1 . It was found that Langmuir and pseudo-second order kinetic models fitted TC adsorption process well. Further photocatalytic studies showed that CoO loaded g-C3 N4 was active for TC photodegradation, although the photocatalytic reaction rate constant was lower than that of native g-C3 N4 . CoO nanoparticles loading on g-C3 N4 played the major role of adsorption sites rather than cocatalyst for photocatalysis. We believe that the developed CoO/g-C3 N4 could be a potential adsorptive photocatalyst for antibiotic pollutants removal from wastewater. Graphical abstract: Image 1 Highlights: NH4 Cl was adopted to enhance the specific surface area of g-C3 N4 . CoO loaded g-C3 N4 was efficient for tetracycline (TC) removal. A high adsorption capacity of 391.4 mg g −1 for TC was obtained over CoO/g-C3 N4.